Cream jengkol seed extract 8% (Archidendron pauciflorum) inhibited the increase melanin amount in the skin of guinea pigs (Cavia porcellus) exposed to ultraviolet-B rays - Rafiah Sirikit Saenong; Wimpie Pangkahila; AAGP Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: The exposure to UV rays on the skin causes hyperpigmentation and premature aging. Hyperpigmentation is caused by an increase of melanin count in the epidermal skin layer. The abundant natural resources that come from Indonesia and have the potential to be good antioxidants are jengkol seeds. The aim of this research was to prove that 8% jengkol seeds (Archidendron pauciflorum) extract cream could inhibit the increase of melanin count in the skin of guinea pig (Cavia porcellus) exposed to ultraviolet B rays. Method: This design of this research is an experimental research with the post-test only control group design. This research used 36 male guinea pigs (Cavia porcellus), local strains, aged 3 months with a body weight of 300-350mg, divided into 2 groups, each of which was 18. The research was conducted for 2 weeks, then a tissue biopsy was carried out as a histological preparation and then the Masson-Fontana staining was carried out. Results: The results showed that the mean value of melanin count for the base cream group was 20.851 ± 1.777%, whereas in the treatment group which applied with 8% jengkol seeds extract cream showed the mean value of 1.289 ± 0.391% (p <0,001). This indicated that the base cream group has a bigger melanin count than the jengkol seeds extract group. Conclusion: The 8% jengkol seeds (Archidendron pauciflorum) extract cream inhibited the increase of melanin